Characterizing drivers of Asia's black elephant disaster risks - Lin, Yolanda C. (2023)
Asia has the fastest growing population and economy, but it is also the most disaster-prone region in the world. Resilience to disaster impacts from natural hazards will be key to the long-term sustainability of this rapidly growing region. The first step to building resilience is to identify the key threats that this region faces. We describe these key threats as Black Elephants: a cross between a “black swan” and the proverbial "elephant in the room" — they are extreme events that are known but difficult to address and often ignored. We examine the primary drivers of these looming risks and find that the drivers include underestimated or intensifying hazards, growing exposure, high vulnerability, and unaccounted complexities from multi-hazard events. In mitigating these key risks, we discuss psychological barriers to action and highlight the importance of information, language, and hope. The known but complex impacts from natural hazards in Asia must be further acknowledged and managed in order to build a more sustainable, resilient future in an increasingly globally connected world.